حدود نظر الخاطب إلى المخطوبة دراسة مقاصدية - خياري إبراهيم (University of Eloued جامعة الوادي, 2023)
يتناول هذا البحث بيان أحد أهم أحكام الخِطبة ومقاصدها العظيمة، ألا وهو استحباب النظر بين الخاطب والمخطوبة قبل الزواج جلبا للمصلحة بين الزوجين. وقد اختلف الفقهاء في حدود نظر الخاطب إلى مخطوبته، لكون الأمر بالنظر جاء في الأحاديث مطلقا غير مقيد، فجاء هذا البحث لبيان أقوال الفقهاء في ذلك واختيار القول الذي يوافق المقصد الشرعي من تشريع النظر في الخطبة. Abstract : This research addresses the most crucial provisions of engagement and its great purposes, which is the desirability of looking between the suitor and the fiancée before marriage so as to to bring about the interest between the spouses. The islamic jurists differed in how the suitor should look at his fiancée within limits that because it takes to look in the hadiths absolutely and not restricted. So this research came to clarify the sayings of the islamis jurists in that and to choose the saying that mostly agrees with the legitimate intent of the engagement.
Keywords: الخطبة؛ حدود النظر؛ المخطوبة.; Betrothal; sightlines; betrothed